Changes in the microbiological, physicochemical properties of Chinese traditional fermented Suan rou at ripening fermentation. Issue 11 (4th September 2021) - Zeng, Xuefeng; Meng, Ju; Zhang, Wei; He, Laping; Deng, Li; Ye, Chun
Abstract: This study characterized the changes in the microbiological, physicochemical properties of Suan rou during fermentation via three different techniques (Technique A is a traditional production process. Based on technique A, technique B adds a total of 200 g of sucrose to the thinly sliced meat, and technique C changes the amount of salt in the thinly sliced meat to 200 grams.). Compared to batch A, the samples from batches B and C featured more rapid reduction in pH and generated more TA. Myofibrillar proteins in batches B and C showed higher degradation rate, and several low‐molecular‐weight metabolites were determined on the basis of sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS‐PAGE) gel lanes. The contents of thiobarbituric acid (TBARS) and total volatile base nitrogen (TVB‐N) and the growth of spoilage bacteria and pathogens were suppressed in the three batches. A relatively compatible acid–salinity proportion was presented in the Suan rou of batches A and B compared with that of batch C. The results show that the Suan rou made by B technology was more palatable acid flavor and abundant nutrition. Abstract : Suan rou is a uniquely tasty and highly safe meat product made by traditional natural fermentation and deeply favored by local consumers. This study characterized the changes in the microbiological and physicochemical properties of Suan rou during fermentation via three different techniques (i.e., A, B, and C). These results show that the Suan rou made by B technology had the most palatable acid flavor and abundant nutrition among the three different batches of Suan rou.